Rethinking the welfare state : the prospects for government by voucher - Daniels, Ronald J. (Ronald Joel), 1959- (Routledge, 2005)
This book offers a comprehensive and comparative analysis of social welfare policy and explores the effectiveness of the voucher system as a solution to problematic areas in the welfare programme.